Captains of Industry and the Subversion of the Professional Ideal in Charlotte Brontë's The Professor and Shirley. (2nd October 2015) - Nyborg, Erin
Abstract : Robert Moore's reformation as a mill owner in Shirley and his decision to marry for love rather than money has been explained as a process of domestication. However, it is more productive to consider this reformation in light of the emergent professional service ideal in the Victorian period. Thomas Carlyle, Samuel Smiles and John Ruskin all presented ideal versions of the professionalized mill owner. Charlotte Brontë engages with this ideal in her depictions of mill owners in both The Professor and Shirley, but challenges and questions the possibilities for personal and professional morality to lead to success without being compromised by personal pride.